Role of Angiopoietin-2 in Vascular Physiology and Pathophysiology - Akwii, Racheal G. (Cells, 2019)
Angiopoietins 1–4 (Ang1–4) represent an important family of growth factors, whose activities are mediated through the tyrosine kinase receptors, Tie1 and Tie2. The best characterized are angiopoietin-1 (Ang1) and angiopoietin-2 (Ang2). Ang1 is a potent angiogenic growth factor signaling through Tie2, whereas Ang2 was initially identified as a vascular disruptive agent with antagonistic activity through the same receptor. Recent data demonstrates that Ang2 has context-dependent agonist activities. Ang2 plays important roles in physiological processes and the deregulation of its expression is characteristic of several diseases. In this review, we summarize the activity of Ang2 on blood and lymphatic endothelial cells, its significance in human physiology and disease, and provide a current view of the molecular signaling pathways regulated by Ang2 in endothelial cells.